2011
DOI: 10.1590/s0080-62342011000300032
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à qualidade de vida de jovens com diabetes mellitus do tipo 1

Abstract: The objective of this study was to perform a literature review of the factors that may influence the Health Related Quality of Life (HRQL) of adolescents with type 1 diabetes mellitus using the PICO strategy. PubMed/ MEDLINE, ISI Web of Knowledge and EMBASE were the databases used. A larger survey of articles was possible by combining standardized and non-standardized descriptors. Though HRQL is a specific construct used to evaluate aspects related to the repercussions of health, illness, and treatment, it app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
1
3
0
7
Order By: Relevance
“…The four groups had total QOL classified with good scores (Table 3), thus, the T1DM-FG and T1DM-MG had better scores compared with FCG. Studies indicate that there are no major differences in QOL between sexes regarding T1DM, which corroborates with the findings of the present study 27,28 . The FCG had the worst scores when assessing QOL in all the domains.…”
Section: Discussionsupporting
confidence: 93%
“…The four groups had total QOL classified with good scores (Table 3), thus, the T1DM-FG and T1DM-MG had better scores compared with FCG. Studies indicate that there are no major differences in QOL between sexes regarding T1DM, which corroborates with the findings of the present study 27,28 . The FCG had the worst scores when assessing QOL in all the domains.…”
Section: Discussionsupporting
confidence: 93%
“…During a review study, Novato and Grossi (2011) identified six main factors that played a role in health related quality of life in adolescents with T1DM: sociodemographic factors, psychosocial aspects, T1DM treatment, family relationships, metabolic control and hyperglycemia. The author's findings also showed that health related quality of life is not controlled by biological factors alone and that patient treatment should encompass social, psychological and assistance aspects, among others.…”
mentioning
confidence: 99%
“…16 , como a melhora da qualidade de vida e da alimentação, manutenção de níveis de estresse e exercício físico 8 . Uma boa qualidade de vida é de extrema importância para os pacientes com DM, assim, com o desenvolvimento da doença se faz necessário a adoção de novos hábitos e comportamentos para efetivação do tratamento intensivo, os quais nem sempre são encarados com facilidade 17,18 .…”
Section: Revisão De Literatura Atenção à Saúdeunclassified